2021
DOI: 10.3390/s21072502
|View full text |Cite
|
Sign up to set email alerts
|

Health-BlockEdge: Blockchain-Edge Framework for Reliable Low-Latency Digital Healthcare Applications

Abstract: The rapid evolution of technology allows the healthcare sector to adopt intelligent, context-aware, secure, and ubiquitous healthcare services. Together with the global trend of an aging population, it has become highly important to propose value-creating, yet cost-efficient digital solutions for healthcare systems. These solutions should provide effective means of healthcare services in both the hospital and home care scenarios. In this paper, we focused on the latter case, where the goal was to provide easy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…We started by introducing our conceptual nanoEdge service model for enabling efficient distributed local edge computing. Then we presented the results of our study related to dynamic resource-aware service orchestration [29] and the integration of Blockchain with Edge Computing for achieving sufficient level of privacy and trust between various stakeholders of distributed e-health and e-welfare services [30]. As the fourth contribution, we proposed and simulated an algorithm for edge-cloud orchestration to minimize the usage of system resources, while maximizing the number of accepted latency-limited task requests [31], which is especially important latency and mission-critical medical applications, such as surgical navigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We started by introducing our conceptual nanoEdge service model for enabling efficient distributed local edge computing. Then we presented the results of our study related to dynamic resource-aware service orchestration [29] and the integration of Blockchain with Edge Computing for achieving sufficient level of privacy and trust between various stakeholders of distributed e-health and e-welfare services [30]. As the fourth contribution, we proposed and simulated an algorithm for edge-cloud orchestration to minimize the usage of system resources, while maximizing the number of accepted latency-limited task requests [31], which is especially important latency and mission-critical medical applications, such as surgical navigation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, when moved to a hospital, the patient treatment service would be further extended with hospital instrumentation. Blockchain edge architecture: In [30], we studied the integration of BC with EC for enabling secure and trusted distributed telemedicine services. The proposed approach improves data privacy protection by 1) limiting the propagation of sensitive data instead of sending all data to the cloud, and 2) enabling the local anonymization of data that need to be sent for processing at public servers.…”
Section: Local Edge Service Orchestrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors revealed the scalable feature of clouds which improved the round-time of sensor applications. Also, authors of [45] discussed how low-latency could be improved in healthcare applications when edge devices were included in the monitoring system.…”
Section: Performance Metric-specific Rmmentioning
confidence: 99%
“…If the Internet connection with the fog and cloud servers fails, local intelligent processing helps to make a decision to solve the problem on the spot. The number of approaches to organize computing include the edge–cloud IoT model, the local edge–cloud IoT model [ 11 ], nanoEdge [ 12 ], and the software-defined network controller in the edge server [ 10 ]. Edge computing increases the efficiency of resources that are used by reducing the amount of data transferred between end systems and centralized cloud servers [ 9 ].…”
Section: Introductionmentioning
confidence: 99%